2013
DOI: 10.1177/0741932513486298
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Point-of-View Video Modeling

Abstract: Video-based modeling (VBM), a category of video-based instruction (VBI), is the process of recording a model engaged in a behavior with the intended goal that the video will be viewed and the desired behavior imitated (Delano, 2007;Hitchcock, Dowrick, & Prater, 2003). VBM has proven to be effective for teaching and improving a variety of skills for individuals with autism spectrum disorder (ASD) and developmental disabilities (DD; Bellini &

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 42 publications
2
39
0
2
Order By: Relevance
“…Despite the evidence supporting the use of point-of-view video models as an effective intervention for individuals with ASD, VMs employing adults, peers, and VSMs are the most frequently used intervention for social skills instruction (Fragale 2014;Mason et al 2013). In a meta-analysis of the efficacy of point-of-view video modeling, Mason et al (2013) identified a study by Tetreault and Lerman (2010) as the only study which examined point-of-view video modeling and social skills.…”
Section: Advantages Of Point-of-view Video Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the evidence supporting the use of point-of-view video models as an effective intervention for individuals with ASD, VMs employing adults, peers, and VSMs are the most frequently used intervention for social skills instruction (Fragale 2014;Mason et al 2013). In a meta-analysis of the efficacy of point-of-view video modeling, Mason et al (2013) identified a study by Tetreault and Lerman (2010) as the only study which examined point-of-view video modeling and social skills.…”
Section: Advantages Of Point-of-view Video Modelingmentioning
confidence: 99%
“…In a meta-analysis of the efficacy of point-of-view video modeling, Mason et al (2013) identified a study by Tetreault and Lerman (2010) as the only study which examined point-of-view video modeling and social skills. Mason et al suggested that the effectiveness of point-of-view video modeling in teaching social skills was inconclusive given the limited research.…”
Section: Advantages Of Point-of-view Video Modelingmentioning
confidence: 99%
See 3 more Smart Citations